Diabetic retinopathy: in vitro and clinical studies of mechanisms and pharmacological treatments - Saker, Saker (2016)
Diabetic retinopathy (DR) is the leading cause of visual impairment in the working-age population in developed countries and thus is one of the major ocular health problems worldwide. Diabetes seems to have paradoxical effects on the microvasculature in different tissues. The concentration of glucose in the cellular microenvironment determines the cells ability to proliferate, as well as its permeability, and react to different cytokines. The main cause of visual loss in diabetic eye disease is caused by an increase in microvascular endothelial permeability which leads to vessel leakage and fluid build-up, diabetic macular oedema (DMO). Endothelial cell permeability is influenced by multiple factors which have not been fully elucidated, particularly in human models. In addition, the gene and protein expression between retinal and choroidal endothelial cells, even in humans, has been shown to be affected differently by diabetes. Current treatments for DMO include steroid such as dexamethasone (DEX) and anti-vascular endothelial growth factor (VEGF) drugs (e.g. ranibizumab, Novartis). These target reducing vascular leakage in the macula once it has occurred, but do not attempt to treat the underlying pathology and evidence suggests treatment does not result in a completely dry macula in most cases. The ideal treatment for DMO should improve vision and improve morphological changes in the macula. With the introduction of microperimetry, we are able to determine macular sensitivity and to correlate it with a precise location of oedema. The aim of this project was to investigate, in vitro, the role of hyperglycaemia in the pathogenesis of DR through effects on the proliferation, vascular permeability and/or alteration in adhesion molecule expression of the human ocular micro-vascular endothelial cells (EC). This was supplemented with clinical studies on pharmacological treatments for DMO.